Characterization of scaffold library to build scaffolds for bones and cartilages - Wan Mohd Firdaus Wan Ahmad (2009)
The use of Computer Aided System for Tissue Scaffold (CASTS) which is an auxiliary platform developed for Pro/ENGINEER to fabricate scaffolds satisfies the need for a system to generate scaffolds of complex designs in order to customize the scaffold according to the patient s specifications. 13 different configurations from a range of polyhedral shapes were available for selection. Due to its complexity, scaffolds were fabricated using Selective Laser Sintering (SLS) technology, which is a Solid Free Form (SFF) technique. The human is bone is layered with functional gradients to satisfy the one or more specific functions that it has to perform. Hence, functional gradients were also utilized in scaffolds to satisfy the biological, anatomical and mechanical requirements of bone [2]. The application of functional gradients were employed in the scaffolds ensures proper transfer of nutrients and prevent the delamination of the scaffold interface. Scaffolds designed using CASTS consist of cells which can be individually tailored to attain specific pore sizes or porosity. As such, the ASTM standard D1621-04a: Standard Test Method for the Compressive Properties of Cellular Solids was adopted to attain the compressive stiffness for mechanical characterization. These scaffolds were fabricated using polycaprolactone (PCL) and the introduction of 10% weight of hydroxyapatite (HA) which is a major constituent of bone, improves cell adhesion and the mechanical properties of scaffolds. Specimens were sent for compression using the Instron Universal 5569 at a strain rate of 2.5 mm/s at up to 0.06 strain. ii It was found that the PCL-HA 10% scaffolds of 40% porosity fabricated using CASTS have a compressive stiffness value of 1-104 MPa while the 60% and the 80% scaffolds have a range of 10-29 MPa and 0.9-6.2 MPa respectively. The design of PCL-HA 10% scaffolds using Configuration 10 was found to be suitable for the replication of the human mandibular bone as it was within the desired compressive stiffness range and its simplicity in generating functional gradients.